Influence Types of Startup on Hydrothermal Scheduling - Ignatius Riyadi Mardiyanto; Hermagasantos Zein; Adi Soeprijanto (Universitas Ahmad Dahlan, 2018)
The energy costs of a power plant consist of startup cost and cost of power usage. In contrast to the existing literature, this study introduces at startup cost based on the duration of thermal power plant downtime. The approach of startup cost function in this research is done by using startup type. Startup of a steam power plant depends on its condition. Generally, there are three types of startup the power plant when the turbine temperature is still very high, i.e. hot start, very hot start and very-very hot start. This paper uses multistage optimization to solve the problem of hydrothermal scheduling with including the startup type cost in the objective function. The simulation results showed operating cost savings when the objective function for optimization also consider the cost based on startup type i.e. when compared with the optimization result which the objective function does not take the cost of startup type.